2006
DOI: 10.1093/aje/kwk029
|View full text |Cite
|
Sign up to set email alerts
|

Disaster-related Stress as a Prospective Risk Factor for Hypertension in Parents of Adolescent Fire Victims

Abstract: Life stress has been related to hypertension in various studies, but well-designed research carried out in disaster settings is scarce. Moreover, most research focuses on the primary victims and disregards effects on their caregivers. In a prospective, population-based cohort study, the authors tested the hypothesis that parents of adolescents who had been involved in the Volendam, Netherlands, pub fire on January 1, 2001 (n = 418) were more at risk of developing hypertension than parents from the same communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…A study in South Africa suggested that self-reported diagnosis of hypertension is more common among those with anxiety disorders, depressive disorders and comorbid anxiety-depression compared to those without a mental disorder [10]. Our findings about having controlled blood pressure is harder in the presence of psychological factors and mental disorders such as anxiety and depression were consistent with those of the several studies [11][12][13][14][15]. Rutledge and Hogan reported an overall increased hypertension risk among anxious subjects although the hypertension risk did not reach significance.…”
Section: Discussionsupporting
confidence: 90%
“…A study in South Africa suggested that self-reported diagnosis of hypertension is more common among those with anxiety disorders, depressive disorders and comorbid anxiety-depression compared to those without a mental disorder [10]. Our findings about having controlled blood pressure is harder in the presence of psychological factors and mental disorders such as anxiety and depression were consistent with those of the several studies [11][12][13][14][15]. Rutledge and Hogan reported an overall increased hypertension risk among anxious subjects although the hypertension risk did not reach significance.…”
Section: Discussionsupporting
confidence: 90%
“…The association between acute stress and hypertension was evaluated in only three studies, 8,12,13 which had inconsistent results. The case-control study showed an inverse association in men and women, 8 but the probability of a recall bias cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…One of the cohort studies showed a null association 12 and the other a positive association. 13 From the studies of chronic stress, five reported at least one significant risk for hypertension among several measures of stress, 8,9,14,15,18 and two were negative. 16,17 The positive studies had a mean average score of quality of 6.6, in comparison with a score of 7.5 for the two studies with negative findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations